Epidemiology of bovine cysticercosis and associated economic losses in the state of Rio Grande do Sul, Brazil - Henckel, Deise Janice (2020)
Bovine cysticercosis (BCC) is the most frequently detected zoonosis in Brazilian slaughterhouses and is considered a problem for public health and beef production chain, requiring epidemiological studies focusing on evaluating its prevalence, spatial distribution, and economic losses in order to improve and adopt specific strategies for BCC control. Thus, this study focused to establish BCC prevalence and spatial distribution in the state of Rio Grande do Sul, Brazil, and estimate the economic losses for cattle farmers suppliers of one exporter slaughterhouse. A set of 70,591 bovine carcasses were postmortem inspected from 2019 to 2020, which came from 134 municipalities located in eight distinct regions in the state of Rio Grande do Sul. The prevalence found was 3.44% (C.I. 95% 3.30–3.57%), and animals infected with unviable cysticerci were more frequently detected (70.56%) than those carrying viable ones (29.44%). The most frequent destination of carcasses and viscera was non-export (65.48%), followed by freezing/salting (25.41%), heat treatment (8.74%), and rendering (0.37%), resulting in a total economic burden of at least US$ 167,868.53 for cattle farmers. Some regions had higher risk for BCC occurrence, such as Porto Alegre, Caxias do Sul, Santa Maria, Ijuí, and Passo Fundo (OR > 1, p < 0.05), respectively. These results highlight the need of adopting prophylactic measures, mainly in specific areas, in order to control BCC and reduce the economic losses for beef production chain.